Indentation size effect in unirradiated and ion-irradiated 800H steel at high temperatures. (1st February 2018) - Prasitthipayong, A.; Vachhani, S.J.; Tumey, S.J.; Minor, A.M.; Hosemann, P.
Abstract: Nanoindentation is a widespread and useful method for evaluating mechanical properties at the sub-micron length scale. However, the indentation size effect remains a major obstacle to obtain meaningful macroscopic mechanical properties from small volume testing. This work systematically addresses the Indentation Size Effect (ISE) phenomenon as a function of temperature and defect density in an austenitic Fe-Cr-Ni alloy (800H) to establish the baseline for nanoindentation testing of ion-irradiated alloys in environmental conditions. The 800H steel sample was irradiated with 70 MeV Fe 9+ at 450 °C to the total dose of 20.68 dpa. All samples were tested up to 300 °C in order to quantify the effect of temperature on the indentation size effect. It was found that in all cases, the ISE is less pronounced at high temperatures due to the increase of the plastic zone size. For the same grain orientation, the ISE is less pronounced in the irradiated 800H at all temperatures. Graphical abstract: Image 1